Socio-economic status and elderly adult mortality in rural Ghana :|bevidence from the Navrongo DSS - Khagayi, Sammy (My University, 2010)
Introduction: In Africa, elderly adult mortality, just like many issues affecting the old has not been adequately addressed by research. This study explored the relationship between socioeconomic status (SES) and elderly adult mortality in an economically deprived region of rural Ghana. Methods: Data from the Navrongo DSS was used for the analysis. SES was determined from the asset data using principal component analysis. A total of 15030 adults aged over 60 years were included in the study, out of which 1315 died. We investigated the above relationship using Cox proportional hazards regression methods while controlling for other variables. Results: Socioeconomic status (SES) was found not to be a determinant of elderly mortality. Compared to the lowest SES quintile, the adjusted hazards ratios were, 0.94 (95%CI: 0.79–1.12) for second quintile, 0.91 (95%CI: 0.76–1.08) for third quintile, 0.89 (95%CI: 0.75–1.07) for fourth quintile and 1.02 (95%CI: 0.86–1.21) for the highest income quintile. However, living without a spouse [HR=1.98, 95%CI: 1.74–2.25], being male [HR=1.80, 95%CI: 1.59–2.04] and age [HR=1.05, 95%CI: 1.04– 1.05] were significant factors for elderly adult mortality. Conclusion: These results indicate that companionship, social and family ties in the health of the elderly adults are of more importance than the socioeconomic status of the household. Efforts should therefore be made to support the elderly, such as stipend for the elderly adults, especially those living alone; lowering the provision of free medical care in public hospitals to cover people over the age of 60 and not just 70 year olds and above as is currently done; encourage family care for the elderly relatives through provision of an elderly caretaker allowance among others.
MSc(Med)Population Based Field Epidemiology, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: adult mortality; socio-economic status; Navrongo, Ghana